1986
DOI: 10.1029/jb091ib04p0d413
|View full text |Cite
|
Sign up to set email alerts
|

Impact craters of Venus: Analysis of Venera 15 and 16 data

Abstract: From description of impact craters on Venus and crater size‐and‐depth distributions, models are developed that analyze the size‐distribution curve and radar‐bright haloes around fresh craters. The dense Venusian atmosphere has a strong influence on cratering. The estimated age of the surface of the area under study is from 0.5 to 1.0×109 years. The estimated rate of resurfacing during this time interval is about 0.04 to 0.8 cm/106 years. The lithosphere of Venus seems to be sufficiently rigid to sustain crater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
75
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(78 citation statements)
references
References 8 publications
3
75
0
Order By: Relevance
“…The dense atmosphere on Venus causes meteoroids to be disrupted in the atmosphere so that the smallest impact crater on Venus is a few km in diameter. The longer path length causes meteoroids entering the atmosphere at low angles to be preferentially filtered out, and the size-frequency distribution of craters may be deficient in low-angle impacts up to 20-30 km in diameter (Tauber and Kirk 1976;Ivanov et al 1986;Ivanov 1990;Herrick and Phillips 1994). Therefore, we surveyed only craters >30 km in diameter.…”
Section: Venusian Datamentioning
confidence: 99%
See 1 more Smart Citation
“…The dense atmosphere on Venus causes meteoroids to be disrupted in the atmosphere so that the smallest impact crater on Venus is a few km in diameter. The longer path length causes meteoroids entering the atmosphere at low angles to be preferentially filtered out, and the size-frequency distribution of craters may be deficient in low-angle impacts up to 20-30 km in diameter (Tauber and Kirk 1976;Ivanov et al 1986;Ivanov 1990;Herrick and Phillips 1994). Therefore, we surveyed only craters >30 km in diameter.…”
Section: Venusian Datamentioning
confidence: 99%
“…Meteoroids entering the venusian atmosphere are disrupted by aerodynamic drag forces. The meteoroid will deform and break apart upon entry, and small meteoroids, apparently, will explode in the atmosphere so that no craters below ~2 km in diameter form on Venus (Tauber and Kirk 1976;Ivanov et al 1986). For larger meteoroids, the fragments will disperse.…”
Section: Craters <15 Km In Diametermentioning
confidence: 99%
“…A population of impact craters was found that suggested a mean surface age for the studied area to be 0.5 to 1 b.y. [Ivanov et al, 1986]. These discoveries suggested a planetary geology that is very different from that of Earth.…”
Section: History Of Venus Explorationmentioning
confidence: 99%
“…The age of the surface of Venus is relatively young, probably a few hundred Ma (Ivanov et al, 1986;Campbell et al, 1991;Phillips et al, 199Ia), but older than that of the terrestrial oceanic crust, which has a mean age of about 100 Ma. In summary, the surface of Venus appears to be dominated by basaltic volcanism, and the elevated regions are crumpled-up basaltic crust.…”
Section: Venusmentioning
confidence: 99%